2006
DOI: 10.1227/01.neu.0000210364.29290.c9
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Acute Subdural Hematomas

Abstract: RECOMMENDATIONS(see Methodology) Indications for Surgery • An acute subdural hematoma (SDH) with a thickness greater than 10 mm or a midline shift greater than 5 mm on computed tomographic (CT) scan should be surgically evacuated, regardless of the patient's Glasgow Coma Scale (GCS) score. • All patients with acute SDH in coma (GCS score less than 9) should undergo intracranial pressure (ICP) monitoring. • A comatose patient (GCS score less than 9) with an SDH less than 10-mm thick and a midline shift less tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
421
2
16

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 394 publications
(444 citation statements)
references
References 31 publications
5
421
2
16
Order By: Relevance
“…Age, Glasgow Coma Scale score, and pupillary reactivity are known prognostic indicators in patients with acute SDH. 4,6) In some studies, SDH volume and midline brain shift have also been related to poor outcome. 4,9,14) This study is the first to report the effect of microbleeds on prognosis in patients with acute SDH.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Age, Glasgow Coma Scale score, and pupillary reactivity are known prognostic indicators in patients with acute SDH. 4,6) In some studies, SDH volume and midline brain shift have also been related to poor outcome. 4,9,14) This study is the first to report the effect of microbleeds on prognosis in patients with acute SDH.…”
Section: Discussionmentioning
confidence: 99%
“…4,6) In some studies, SDH volume and midline brain shift have also been related to poor outcome. 4,9,14) This study is the first to report the effect of microbleeds on prognosis in patients with acute SDH. Our results support a previous study that reported a relationship between microbleeds and prognosis in patients with moderate and severe traumatic brain injury and diffuse axonal injury.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations